Multi‐length or 24 cm ureteric stent? A multicentre randomised comparison of stent‐related symptoms using a validated questionnaire. (9th August 2012) - Calvert, Robert C.; Wong, Kee Y.; Chitale, Sudhanshu V.; Irving, Stuart O.; Nagarajan, Muthuswamy; Biyani, Chandra S.; Browning, Anthony J.; Young, James G.; Timoney, Anthony G.; Keeley, Francis X.; Burgess, Neil A.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? One of the suggested factors for stent‐related symptoms is that excess distal intravesical stent mass may cause bladder irritation. There is a lack of studies investigating this in a randomised controlled fashion using a validated questionnaire. This study compared two of the most commonly used length of stents (a 30 cm multi‐length vs a 24 cm long stent) and showed no significance difference in stent‐related symptoms in patients with either of these stents. Objective To investigate whether excessive redundant intravesical stent component contributes to the severity of stent‐related symptoms in patients with a ureteric stent. We compared stent‐related symptoms in patients who had either a standard 24 cm or multi‐length ureteric stent. Patients and Methods In all, 162 patients with upper urinary tract calculi requiring ureteric stent insertion were randomised to receive either a 6 F × 24 cm ContourTM or multi‐length 6 F × 22–30 cm Contour VLTM stent. Patients were requested to complete the validated Bristol Ureteric Stent Symptom Questionnaire (USSQ) at 1 and 4 weeks after stent insertion and 4 weeks after removal. The mean scores for each domain of the USSQ for both groups were compared using the Student's t‐test. Any adverse events, e.g. stent migration, early removal of stent due to stent‐related symptoms and failure of stent insertion, were also recorded. Results In all, 153 patients who had successful stent insertion were requested to complete the USSQ and 74% of patients returned at least the week 1 questionnaire. At 1 and 4 weeks with the stent in situ, comparison of the mean scores showed no significant difference in urinary symptoms, pain, general health, work performance, sexual dysfunction and number of days patients stayed in bed or reduced their routine activities. Three (2%) patients had their stent removed early due to stent‐related symptoms and five (3%) had failed stent insertion. Conclusions This study did not find any difference in symptoms between the 24 cm or multi‐length Contour stents. However, the study was not powered to detect small differences particularly for the pain symptom domain. Stents should only be used sparingly and the stent dwell‐time should be minimised.